Financial Literacy, Governance Mechanisms, and Innovation Capability in Explaining SME Performance The Moderating Role of Organizational Culture - Fran Sayekti; Siti Resmi; Reza Widhar Pahlevi (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2026)
Small and medium-sized enterprises (SMEs) play a vital role in regional economic development; however, their ability to achieve sustainable performance is often influenced by internal capabilities and governance practices. Financial literacy and SME governance are considered important factors in enhancing innovation capability, which may subsequently improve business performance. Organizational culture may also strengthen or weaken the effectiveness of innovation capability in driving performance outcomes. This study aims to examine the effects of financial literacy and SME governance on innovation capability and SME performance. It also investigates the moderating role of organizational culture in the relationship between innovation capability and SME performance. The study employed a quantitative research design involving SMEs in the Special Region of Yogyakarta, Indonesia. Using a purposive sampling technique, data were collected from 176 SME owners or managers. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software to test the proposed relationships among variables. The results reveal that financial literacy and SME governance have positive and significant effects on innovation capability. SME governance also exerts a positive and significant direct influence on SME performance. However, financial literacy does not significantly affect SME performance directly. Furthermore, innovation capability does not have a significant impact on SME performance. The findings also indicate that organizational culture does not significantly moderate the relationship between innovation capability and SME performance. This study highlights the importance of strengthening financial literacy and implementing effective governance practices to enhance innovation capability among SMEs. The absence of a moderating effect of organizational culture suggests that other contextual factors may play a more critical role in translating innovation capability into superior performance. These findings provide valuable insights for SME practitioners and policymakers in designing strategies to improve SME competitiveness and sustainability.